FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN (Studi Kasus Desa Pangi Kecamatan Suwawa Timur Kabupaten Bone Bolango - Ramlah Alkatiri; Joice Machmud; Melti Botutihe (LPPM Universitas Muhammadiyah Gorontalo, 2025)
This study aims to determine the dominant factors that cause poverty in Pangi Village, East Suwawa District, which is the object of this research. This study uses a qualitative approach, using interviews in the study. The results showed that the factors that caused poverty in Pangi Village, East Suwawa District, were caused by absolute poverty factors, namely poverty caused by income inequality factors, cultural factors, natural conditions, access to information that was still limited. Poverty that occurs is not due to education and skills factors but rather income inequality factors, cultural factors, socio-economic conditions and not having family assets